Incidencia de los Impuestos Directos e Indirectos en el Crecimiento Económico del Perú, 1990-2018 - Reyes Pérez, Xiomara Fátima (2019)
This paper seeks to know the incidence of direct and indirect taxes on the economic growth of Peru during the period 1990-2018. The Income Tax (IR) represents direct taxes and the General Sales Tax (IGV) on indirect taxes. In addition, the Non-Financial Expenditure of the General Government and Private Fixed Gross Investment were added, being collected in the statistical database of the Central Reserve Bank of Peru, INEI and SUNAT, the Ordinary Square Minimum (MCO) model was considered, using the econometric software Eviews. The results that correspond to direct taxes with the IR, include positively and indirect taxes such as the IGV in a negative way with respect to the economic growth of Peru. Theoretically with the study by Robert Barro (1990), in his endogenous growth model that incorporates taxes, it demonstrates a double effect of the tax rate on the growth rate. Consequently, there is a tax rate that maximizes the economic growth rate that can be a direct tax and the other rate is the indirect tax that decreases the economic growth rate. In addition, Ilaboya, O & Mgbame, C. (2012) and Mariños, J. & Rosas P. (2015), found empirical evidence, indicating that the signs agree and there is a certain approximation in the coefficients.